Thiolate versus selenolate: structure, stability, and charge transfer properties - Ossowski, Jakub; Wächter, Tobias; Silies, Laura; Kind, Martin; Noworolska, Agnieszka; Blobner, Florian; Gnatek, Dominika; Rysz, Jakub; Bolte, Michael; Feulner, Peter; Terfort, Andreas; Cyganik, Piotr; et al. (ACS nano, 2015)
Selenolate is considered as an alternative to thiolate to serve as a headgroup mediating the formation of self-assembled monolayers (SAMs) on coinage metal substrates. There are, however, ongoing vivid discussions regarding the advantages and disadvantages of these anchor groups, regarding, in particular, the energetics of the headgroup-substrate interface and their efficiency in terms of charge transport/transfer. Here we introduce a well-defined model system of 6-cyanonaphthalene-2-thiolate and -selenolate SAMs on Au(111) to resolve these controversies. The exact structural arrangements in both types of SAMs are somewhat different, suggesting a better SAM-building ability in the case of selenolates. At the same time, both types of SAMs have similar packing densities and molecular orientations. This permitted reliable competitive exchange and ion-beam-induced desorption experiments which provided unequivocal evidence for a stronger bonding of selenolates to the substrate as compared to the thiolates. Regardless of this difference, the dynamic charge transfer properties of the thiolate- and selenolate-based adsorbates were found to be nearly identical, as determined by the core-hole-clock approach, which is explained by a redistribution of electron density along the molecular framework, compensating the difference in the substrate-headgroup bond strength.
Gesehen am 25.06.2020